Embedding collective leadership to foster collaborative inter-professional working in the care of older people (ECLECTIC): Study protocol - Anjara, Sabrina G. (HRB Open Res, 2020)
Background: The National Integrated Care Programme for Older People (NICPOP), formerly NCPOP aims to support older people to live well in their homes by developing primary and secondary care services for older people, especially those with complex needs. The programme develops integrated intermediate care which traverses both hospital and community settings through multidisciplinary and interagency teams. This team-based approach to the integration of health services is a novel innovation in Irish health service delivery and will require, over time, a shift in cultures of care to allow for the development of competencies for inter-professional collaboration across the care continuum. The ECLECTIC project will develop an implementation framework for achieving, maintaining and monitoring competencies for interprofessional collaboration among multi-disciplinary teams charged with delivering care for older people across the continuum from acute to community settings. Design: The ECLECTIC research design has been developed in collaboration with the NICPOP. In phase one of the project, a co-design team will collaborate to define and shape competencies for interprofessional collaboration. Phase two will involve the delivery of a collective leadership intervention over a 10-month period with multidisciplinary professionals working with older people across two geographical regions (Mullingar/Midlands and Beaumont/Dublin North). Each group will comprise of members of two multidisciplinary teams charged with coordinating and delivering care to older people across the continuum of acute to community care. Observations of collaborative inter-professional working will take place before, during, and after intervention. In phase three of the study, analysis of the interview and observation data will be presented to the co-design team in order to develop an implementation framework for future teams. Discussion: The co-design process will develop core competencies and performance indicators for collaborative interprofessional working. The resulting implementation framework will be implemented nationally as part of the NICPOP.